A Culture in Conflict: Skilled Workers and Industrial Capitalism in Hamilton, Ontario, 1860-1914 - Palmer, Bryan D. (McGill-Queen's University Press, 1979)
[This book] is a study of continuity and change in the lives of skilled workers in Hamilton, Ontario, during a period of economic transformation. Bryan D. Palmer shows how the disruptive influence of devel oping industrial capitalism was counterbalanced by the stabilizing effect of the associational life of the workingman, ranging from the fraternal order and the mechanics' institute to the baseball diamond and the "rough music" of the charivari. On the basis of this social and cultural solidarity, Hamilton's craftsmen fought for and achieved a measure of autonomy on the shop-floor through the practice of workers' control. Working-class thought proved equally adaptable, moving away from the producer ideology and its manufacturer-mechanic alliance toward a recognition of class polarization. Making ample use of contemporary evidence in newspapers, labour journals, and unpublished correspondence, the author discusses such major developments in the class conflict as the nine-hour movement of 1872, the dramatic emergence of the Knights of Labor, and the beginnings of craft unionism after 1890. He finds that the concept of a labour aristocracy has litlle meaning in Hamilton, where skilled workers were the culling edge of the working-class movement, involved in issues which directly related to the experience of their less-skilled brethren. More remarkable than the final attainment of capitalist control of the work place, he concludes, are the long-continued resistance of the Hamilton workers and their success in retaining much of their power in the pre-World War I years. –Publisher's description
Available at Internet Archive to readers with print disabilities: https://archive.org/details/cultureinconflic0000palm OCLC: 5527572